2021
DOI: 10.1007/s00362-020-01214-z
|View full text |Cite
|
Sign up to set email alerts
|

The generalized equivalence of regularization and min–max robustification in linear mixed models

Abstract: The connection between regularization and min–max robustification in the presence of unobservable covariate measurement errors in linear mixed models is addressed. We prove that regularized model parameter estimation is equivalent to robust loss minimization under a min–max approach. On the example of the LASSO, Ridge regression, and the Elastic Net, we derive uncertainty sets that characterize the feasible noise that can be added to a given estimation problem. These sets allow us to determine measurement erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…On that note, Burgard et al. 63 showed that l 2 -penalization is equivalent to a robustification against arbitrary measurement errors. However, their results apply to linear-mixed models, and it is uncertain whether they can be extended to GLMMs.…”
Section: Discussionmentioning
confidence: 99%
“…On that note, Burgard et al. 63 showed that l 2 -penalization is equivalent to a robustification against arbitrary measurement errors. However, their results apply to linear-mixed models, and it is uncertain whether they can be extended to GLMMs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we state a framework called min-max robust regression that arises from RO and allows for robust model parameter estimates in the presence of unknown auxiliary data contamination. The following descriptions draw from Bertsimas and Copenhaver (2018) and Burgard et al (2020).…”
Section: Min-max Robust Regressionmentioning
confidence: 99%
“…For further details and applications of RO, see El Ghaoui and Lebret (1997), Markovsky and Van Huffel (2007), and Ben-Tal, El Ghaoui, and Nemirovski (2009). Recent theoretical developments showed that RO has a natural connection to penalized regression (Bertsimas & Copenhaver, 2018;Burgard, Krause, Kreber, & Morales, 2020;Krause, 2019). More precisely, RO can be performed by using norm-based penalization in linear models, such as the elastic net proposed by Zou and Hastie (2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations